SDSS-IV MaNGA: the different quenching histories of fast and slow rotators - Smethurst, Rebecca J.; Masters, Karen L.; Lintott, Chris J.; Weijmans, Anne-Marie; Merrifield, Michael R.; Penny, Samantha J.; Aragón-Salamanca, Alfonso; Brownstein, J.; Bundy, Kevin; Drory, Niv; Law, D.R.; Nichol, Robert C. (Oxford University Press, 2018)
Do the theorised different formation mechanisms of fast and slow rotators produce an observable difference in their star formation histories? To study this we identify quenching slow rotators in the MaNGA sample by selecting those which lie below the star forming sequence and identify a sample of quenching fast rotators which were matched in stellar mass. This results in a total sample of 194 kinematically classified galaxies, which is agnostic to visual morphology. We use u − r and NUV − u colours from SDSS and GALEX and an existing inference package, STARPY, to conduct a first look at the onset time and exponentially declining rate of quenching of these galaxies. An Anderson-Darling test on the distribution of the inferred quenching rates across the two kinematic populations reveals they are statistically distinguishable (3.2σ). We find that fast rotators quench at a much wider range of rates than slow rotators, consistent with a wide variety of physical processes such as secular evolution, minor mergers, gas accretion and environmentally driven mechanisms. Quenching is more likely to occur at rapid rates (τ≲1 Gyr) for slow rotators, in agreement with theories suggesting slow rotators are formed in dynamically fast processes, such as major mergers. Interestingly, we also find that a subset of the fast rotators quench at these same rapid rates as the bulk of the slow rotator sample. We therefore discuss how the total gas mass of a merger, rather than the merger mass ratio, may decide a galaxy’s ultimate kinematic fate.